A fine-scale, broadly applicable index of vocal performance: frequency excursion. (June 2016) - Podos, Jeffrey; Moseley, Dana L.; Goodwin, Sarah E.; McClure, Jesse; Taft, Benjamin N.; Strauss, Amy V.H.; Rega-Brodsky, Christine; Lahti, David C.
Abstract : Our understanding of the evolution and function of animal displays has been advanced through studies of vocal performance. A widely used metric of vocal performance, vocal deviation, is limited by being applicable only to vocal trills, and also overlooks certain fine-scale aspects of song structure that might reflect vocal performance. In light of these limitations we here introduce a new index of vocal performance, 'frequency excursion'. Frequency excursion calculates, for any given song or song segment, the sum of frequency modulations both within and between notes on a per-time basis. We calculated and compared the two performance metrics in three species: chipping sparrows, Spizella passerina, swamp sparrows, Melospiza georgiana, and song sparrows, Melospiza melodia . The two metrics correlated as expected, yet frequency excursion accounted for subtle variations in performance overlooked by vocal deviation. In swamp sparrows, frequency excursion values varied significantly by song type but not by individual. Moreover, song type performance in swamp sparrows, according to both metrics, varied negatively with the extent to which song types were shared among neighbours. In song sparrows, frequency excursion values of trilled song segments exceeded those of nontrilled song segments, although not to a statistically significant degree. We suggest that application of frequency excursion in birds and other taxa will provide new insights into diverse open questions concerning vocal performance, function and evolution. Highlights: We introduce a new method for quantifying vocal performance, 'frequency excursion'. We apply this method to sample questions about vocal performance in three sparrow species. Frequency excursion will help provide new insights into vocal performance and evolution.